Pengaruh Harga dan Citra Merek Terhadap Keputusan Pembelian Kosmetik Hanasui Pada Gen Z - Risah, A.; Rahmawati, Fitri Maulidah (STIE AMKOP, 2025)
This study aims to determine the effect of tax sanctions, service quality, and taxpayer income levels on land and building tax compliance in Alak District, Kupang City. The population in this study was 21,553 registered land and building taxpayers in Alak District in 2024. The sample size of 100 respondents was calculated using the Slovin formula. Data collection used a research questionnaire, which was distributed offline and directly to land and building taxpayers in Alak District. The analysis technique used was multiple linear regression analysis to test the hypotheses. The results of this study indicate that: (1) Tax sanctions affect land and building taxpayer compliance; (2) Service quality affects land and building taxpayer compliance; (3) Income level affects land and building taxpayer compliance; (4) Tax sanctions, service quality, and income level jointly affect land and building taxpayer compliance. Keywords: Tax Sanctions, Service Quality, Income Level, Taxpayer Compliance, Land and Building Tax